Prognosis of Full-Thickness Skin Defects in Premature Infants - Hyung Suk Moon; Jin Sik Burm; Won Yong Yang; Sang Yoon Kang (Archives of Plastic Surgery, 2012)
Background In the extremities of premature infants, the skin and subcutaneous tissue are very pliable due to immaturity and have a greater degree of skin laxity and mobility. Thus, we can expect wounds to heal rapidly by wound contraction. This study investigates wound healing of full-thickness defects in premature infant extremities. Methods The study consisted of 13 premature infants who had a total of 14 cases of full-thickness skin defects of the extremities due to extravasation after total parenteral nutrition. The wound was managed with intensive moist dressings with antibiotic and anti-inflammatory agents. After wound closure, moisturization and mild compression were performed. Results Most of the full-thickness defects in the premature infants were closed by wound contraction without granulation tissue formation on the wound bed. The defects resulted in 3 pinpoint scars, 9 linear scars, and 2 round hypertrophic scars. The wounds with less granulation tissue were healed by contraction and resulted in linear scars parallel to the relaxed skin tension line. The wounds with more granulation tissue resulted in round scars. There was mild contracture without functional abnormality in 3 cases with a defect over two thirds of the longitudinal length of the dorsum of the hand or foot. The patients' parents were satisfied with the outcomes in 12 of 14 cases. Conclusions Full-thickness skin defects in premature infants typically heal by wound contraction with minimal granulation tissue and scar formation probably due to excellent skin mobility.